2019
DOI: 10.1200/jgo.19.00172
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Burkitt Lymphoma in Sub-Saharan Africa Pediatric Units: Results of the Third Prospective Multicenter Study of the Groupe Franco-Africain d’Oncologie Pédiatrique

Abstract: PURPOSETo evaluate the results of an intensive polychemotherapy regimen for Burkitt lymphoma (BL) in sub-Saharan African pediatric centers.PATIENTS AND METHODSChildren with advanced-stage BL (stages II bulky, III, and IV) treated with the GFAOP–Lymphomes Malins B (GFALMB) 2009 protocol in 7 centers between April 2009 and September 2015 were prospectively registered. Treatment regimen contained a prephase with cyclophosphamide followed by 2 induction courses (cyclophosphamide, vincristine, prednisone, high-dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 31 publications
0
39
0
Order By: Relevance
“…5 Furthermore, in equatorial Africa, where BL is the most common childhood cancer, the prognosis of BL is still poor because the intensive therapeutic regimens often result in a severe neutropenia, with fatal consequences in resource poor settings. [6][7][8][9][10] Shortcomings of current BL therapies make the exploration of new therapeutic avenues a substantial and reasonable aim. 7 Therefore, a proper characterization of the TME in BL might be helpful to identify alternative therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…5 Furthermore, in equatorial Africa, where BL is the most common childhood cancer, the prognosis of BL is still poor because the intensive therapeutic regimens often result in a severe neutropenia, with fatal consequences in resource poor settings. [6][7][8][9][10] Shortcomings of current BL therapies make the exploration of new therapeutic avenues a substantial and reasonable aim. 7 Therefore, a proper characterization of the TME in BL might be helpful to identify alternative therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, these burdensome treatments are not as effective in elderly and immunocompromised patients [5]. Furthermore, in equatorial Africa, where BL is the most common childhood cancer, the prognosis of BL is still poor because the intensive therapeutic regimens often result in a severe neutropenia, with fatal consequences in resource poor settings [6][7][8][9][10]. Shortcomings of current BL therapies make the exploration of new therapeutic avenues a substantial and reasonable aim [7].…”
Section: Introductionmentioning
confidence: 99%
“…26,38,40,41,[48][49][50] This is particularly relevant because numerous studies in SSA have demonstrated that abdominal mass has become at least as common as jaw mass as a presenting feature of endemic BL (Figure 1). 17,20,51,52 A recent clinical quality improvement project at the Uganda Cancer Institute is emblematic of the lack of progress in improving outcomes: over a 5-year period (2012-2017), 180 children with pathology-confirmed diagnoses of BL were treated with COM, with resources dedicated to ensuring accurate diagnosis, chemotherapy availability, and treatment compliance. 44 Despite mitigating limitations of access to care, the 4-year OS was 44%, 44 similar to results from clinical trials at the same center from the 1970s.…”
Section: Contemporary Standards and Efforts To Improve Bl Treatment Imentioning
confidence: 99%
“…They were able to reproduce the superior outcomes seen in the earlier experience with a 1-year OS of 60% for patients with advanced-stage disease and a TRM of 12%. 51 Using a modified LMB regimen, they continued to deliver the first 2 induction cycles with cyclophosphamide, vincristine, prednisone, and hdMTX for 2 cycles, followed by hdMTX plus mini-cytarabine (500 mg/m 2 per cycle) for 2 cycles, including 3000 mg/m 2 of MTX over 3 hours. 51 The progress made by GFAOP highlights the necessity for enhanced supportive care along with intensified MTX.…”
Section: Improving Diagnosis and Risk Stratification Of Endemic Blmentioning
confidence: 99%